Identifikasi Struktur Bawah Permukaan Area Tempuran, Magelang, Jawa Tengah dengan Metode Gravitasi GGMplus - Nisrina Hasna Mustofa; Roma Widiyansari; Khafidh Nur Aziz; Denny Darmawan; Laras Anindita Maharani; Aqheela Aphrodita Zainfa; Rahmawati Fitrianingtyas; Ika Maulita (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2025)
This research was conducted in the Tempuran geothermal manifestation area, Magelang, Central Java, specifically in a location with indications of fault structure. The study aims to identify the subsurface structural conditions associated with the fault through the distribution pattern of gravity anomalies. This research used gravity method, with the data are gravity disturbance from GGMplus with a resolution of approximately 220 meters. The gravity disturbance data were processed to obtain Complete Bouguer Anomaly (CBA) data, which were then subjected to upward continuation and forward modeling. The CBA results reveal a high anomaly in the southern part of the study area, extending southwestward, which correlates with the Menoreh Mountains. A low anomaly is found in the northeastern part of the area, corresponding to a lowland region. The 2D modeling results indicate that the study area is composed of rocks with densities ranging from 1.00 g/cm³ to 1.60 g/cm³, interpreted as alluvium; 1.75 g/cm³ to 2.73 g/cm³, interpreted as the Kebobutak Formation; and 2.50 g/cm³, interpreted as deposits from theyoung Sumbing Volcano. Additionally, rocks with densities ranging from 2.40 g/cm³ to 2.77 g/cm³ are interpreted as andesitic intrusions, while rocks with a density of 2.83 g/cm³ are interpreted as dacitic intrusions. The presence of a normal fault is identified within the Kebobutak Formation and the andesitic intrusion, overlain by alluvial deposits.